School Community Empowerment through Artificial intelligence and Augmented reality Literacy at SMAN 2 Barru: Pemberdayaan Masyarakat Sekolah Melalui Literasi Kecerdasan Buatan dan Augmented reality di SMAN 2 Barru - Fakhri, M. Miftach; Kurnia Prima Putra; Dary Mochamad Rifqie; Nur Annafiah; Pramudya Asoka Syukur; Arsyanda (Mattawang: Jurnal Pengabdian Masyarakat, 2024)
SMA Negeri 2 Barru faces significant challenges in integrating technology into education, particularly in enhancing digital literacy among teachers to bridge the skills gap needed for entrepreneurship in the digital era. This community service aims to improve entrepreneurial skills among teachers and students by utilizing AI and AR technology. The program employs an Action Research approach, involving cycles of planning, implementation, observation, and reflection to enhance the participants' technological competencies. The results indicate that the program successfully equipped teachers with essential skills such as market trend analysis using Google Forms, business idea brainstorming with AI, and utilizing AR for product visualization. However, challenges such as limited time and inadequate internet connectivity affected the absorption of the material. Despite these obstacles, the program demonstrated a positive impact on the participants' technological and entrepreneurial abilities, though further improvements in infrastructure and training duration are recommended for future programs. Abstrak SMA Negeri 2 Barru menghadapi tantangan signifikan dalam mengintegrasikan teknologi ke dalam pendidikan, terutama dalam meningkatkan literasi digital di kalangan guru untuk menjembatani kesenjangan keterampilan yang diperlukan dalam kewirausahaan di era digital. Pengabdian ini bertujuan untuk meningkatkan keterampilan kewirausahaan di kalangan guru dan siswa dengan memanfaatkan teknologi AI dan AR. Program ini menggunakan pendekatan Action Research, yang melibatkan siklus perencanaan, pelaksanaan, observasi, dan refleksi untuk meningkatkan kompetensi teknologi para peserta. Hasil menunjukkan bahwa program ini berhasil membekali guru dengan keterampilan penting seperti analisis tren pasar menggunakan Google Form, brainstorming ide bisnis dengan AI, dan memanfaatkan AR untuk visualisasi produk. Namun, tantangan seperti keterbatasan waktu dan konektivitas internet yang kurang memadai mempengaruhi penyerapan materi. Meskipun demikian, program ini telah menunjukkan dampak positif terhadap kemampuan teknologi dan kewirausahaan para peserta, meskipun perbaikan lebih lanjut dalam infrastruktur dan durasi pelatihan direkomendasikan untuk program-program mendatang.